2013
DOI: 10.1093/carcin/bgt354
|View full text |Cite
|
Sign up to set email alerts
|

miR-9 targets CXCR4 and functions as a potential tumor suppressor in nasopharyngeal carcinoma

Abstract: MicroRNA deregulation and pathway alterations have been implicated in nasopharyngeal carcinoma (NPC), a highly invasive and metastatic cancer widely prevalent in Southern China. In this study, we report that miR-9 is commonly downregulated in NPC specimens and NPC cell lines with important functional consequences. The reduced expression of miR-9 was inversely correlated with clinical stages and marked the progression from locoregional to metastatic tumors. The CpG island hypermethylation contributed to miR-9 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
83
0
5

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(96 citation statements)
references
References 47 publications
8
83
0
5
Order By: Relevance
“…Several direct targets of miR-9 such as cyclin D1, Ets1 (Zheng et al, 2013), and CXCR4 (Lu et al, 2013) have currently been identified. Repression of cyclin D1 and Ets1 is involved in miR-9-mediated suppression of the proliferation, invasion and metastasis of gastric cancer cells (Zheng et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several direct targets of miR-9 such as cyclin D1, Ets1 (Zheng et al, 2013), and CXCR4 (Lu et al, 2013) have currently been identified. Repression of cyclin D1 and Ets1 is involved in miR-9-mediated suppression of the proliferation, invasion and metastasis of gastric cancer cells (Zheng et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Repression of cyclin D1 and Ets1 is involved in miR-9-mediated suppression of the proliferation, invasion and metastasis of gastric cancer cells (Zheng et al, 2013). Targeting CXCR4 was found to mediate the suppressive effects of miR-9 in nasopharyngeal carcinoma (Lu et al, 2013). Identification of specific target genes is of great importance in clarifying the functions of miR-9 in curcumin-mediated cytotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-202 may be a potential key regulator resulting in the metastasis of OS, and CALD1 may be the possible therapeutic target. MiR-9 is also a widely studied tumor suppressor miRNA in acute myelocytic leukemia, nasopharyngeal carcinoma and ovarian cancer, even an essential oncogenic miRNA specifically over-expressed in mixed lineage leukemia-rearranged leukemia (Emmrich et al, 2013;Lu et al, 2013;Sun et al, 2013). Furthermore, miR-9 is reported to be up-regulated in breast cancer cells, influencing the expression of E-cadherin, and further leading to increased cell motility and invasiveness and even cancer metastasis (Khew-Goodalland Goodall, 2010;Ma et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Not only has miR-9 been identified as a potential circulating biomarker of advanced NPC [31] , several potential targets and functions of miR-9 have also been reported. Recently, two studies describing putative tumor suppressive mechanisms for miR-9 in NPC have been published [32,33] . Lu et al [32] reported that hypermethylation and subsequent underexpression of miR-9 led to up-regulation of its putative target C-X-C chemokine receptor type 4 (CXCR4), resulting in increased cell growth, migration, and invasion through activation of the Mitogen-activated protein kinase (MAPK) pathway.…”
Section: Human Mirna Expression In Npcmentioning
confidence: 99%
“…Recently, two studies describing putative tumor suppressive mechanisms for miR-9 in NPC have been published [32,33] . Lu et al [32] reported that hypermethylation and subsequent underexpression of miR-9 led to up-regulation of its putative target C-X-C chemokine receptor type 4 (CXCR4), resulting in increased cell growth, migration, and invasion through activation of the Mitogen-activated protein kinase (MAPK) pathway. In contrast, Gao et al [33] postulated a role for miR-9 in modulating the immune response to NPC by targeting several interferon (IFN)-induced genes, multiple members of the major histocompatibility complex (MHC) class I molecule, and a number of interleukins and related genes.…”
Section: Human Mirna Expression In Npcmentioning
confidence: 99%